Prototipe Manipulator Lengan Robot Berbasis Arduino dengan Metoda Kendali Lead-Through - Erwin Sitompul; Sodri Sodri (Politeknik Caltex Riau, 2020)
In this research, a prototype of Arduino-based robot arm manipulator (MLR) controlled with lead-through method is proposed. Through lead-through control methods, the robot movement programming process is replaced by a simple and easy robot movement recording process. The recording process is performed when parts of the MLR are manually moved by the user. Afterwards, the playback process of the recorded movement can be performed. The MLR has 4 degrees of freedom and uses four servo motors to perform rotational movement, upward-downward movement, forward-backward movement, and gripping movement. The servo motors are modified so that each of them has one additional terminal that serves to provide position feedback. On the recording process, the position of all servo motors is recorded on Arduino Uno EEPROM every 200 milliseconds time interval. In the playback process, the recorded position is sent to the servo motors as input, and the MLR repeats the recorded movement. The MLR is tested to move workpieces with accuracy requirement of ± 3cm. MLR is able to repeat the movement to move 1 workpiece for 30 cm displacement with a success rate of 80%. In addition, MLR is able to playback the movement to move 2 workpieces for 60 cm displacement with a success rate of 85%.